About the Influence of Double Bonds in the APPECVD of Acrylate‐Like Precursors: A Mass Spectrometry Study of the Plasma Phase. Issue 4 (7th February 2014) - Nisol, Bernard; Arnoult, Grégory; Bieber, Thomas; Kakaroglou, Alexandros; De Graeve, Iris; Van Assche, Guy; Terryn, Herman; Reniers, François
<x xml:space="preserve">Abstract</x> This work deals with the in‐situ mass spectrometric (MS) characterization of gases during the atmospheric pressure plasma‐enhanced chemical vapor deposition of propyl isobutyrate (PiB) and allylmethacrylate (AMA). By monitoring the fragments of interest, we are trying to understand the mechanisms involved in the plasma synthesis of acrylate‐like coatings. For instance, while CO2+ drastically increases when a PiB/argon plasma is ignited, it decreases in the case of AMA. This trend also appears for other fragments, which leads to the conclusion that while PiB seems to suffer from fragmentation, AMA oligomerizes into the gas phase, resulting in a better protection of the ester functionality.<inline-graphic xlink:href="ark:/27927/pgg59wdqds9" content-type="ppap201300176-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />